Cone Beam Computed Topographic Evaluation and Endodontic Management of a Rare Mandibular First Molar with Four Distal Canals - Nidhi Sinha; Bijay Singh; Akshay Langaliya; Nitin Mirdha; Irfanul Huda; Ashwin Jain (Case Reports in Dentistry)
Root canal system is complex to understand because of its unpredictable nature. It differs for different teeth and for the same teeth in different individuals. Successful endodontic therapy thus depends on the clinician’s ability to anticipate and look for these variations. A mandibular first molar with six root canals represents a rare anatomical variant, particularly when four canals are found in distal root. This case report discusses successful nonsurgical endodontic management of two-root mandibular first molar with four distal canals and two mesial canals reported for the first time in Indian population. Cone beam computed tomography was used as a diagnostic method to confirm the position and presence of 4 root canals in the distal root.